Crystal structure of the Propionibacterium acnes surface sialidase, a drug target for P. acnes-associated diseases. (17th November 2021) - Yu, Angel C Y; Volkers, Gesa; Jongkees, Seino A K; Worrall, Liam J; Withers, Stephen G; Strynadka, Natalie C J
Abstract: Propionibacterium acnes, though generally considered part of the normal flora of human skin, is an opportunistic pathogen associated with acne vulgaris as well as other diseases, including endocarditis, endophthalmitis and prosthetic joint infections. Its virulence potential is also supported by knowledge gained from its sequenced genome. Indeed, a vaccine targeting a putative cell wall-anchored P. acnes sialidase has been shown to suppress cytotoxicity and pro-inflammatory cytokine release induced by the organism, and is proposed as an alternative treatment for P. acnes -associated diseases. Here, we report the crystal structures of the surface sialidase and its complex with the transition-state mimic Neu5Ac2en. Our structural and kinetic analyses, together with insight from a glycan array screen, which probes subtle specificities of the sialidase for α-2, 3-sialosides, provide a basis for the structure-based design of novel small-molecule therapeutics against P. acnes infections.